2021
DOI: 10.3389/fphar.2021.671238
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Topical Gabapentin on Ocular Pain and Tear Secretion

Abstract: Neuropathic ocular pain is a frequent occurrence in medium to severe dry eye disease (DED). Only palliative treatments, such as lubricants and anti-inflammatory drugs, are available to alleviate patients’ discomfort. Anesthetic drugs are not indicated, because they may interfere with the neural feedback between the cornea and the lacrimal gland, impairing tear production and lacrimation. Gabapentin (GBT) is a structural analog of gamma-amino butyric acid that has been used by systemic administration to provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 53 publications
(67 reference statements)
0
22
0
Order By: Relevance
“…Gabapentin (GBT) is a structural analog of gamma-amino butyric acid that is used as an antiepileptic drug as well as to provide pain relief in glaucomatous patients [ 88 ]. GBT also has analgesic and anti-inflammatory properties, so it may be useful as a DED medication [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gabapentin (GBT) is a structural analog of gamma-amino butyric acid that is used as an antiepileptic drug as well as to provide pain relief in glaucomatous patients [ 88 ]. GBT also has analgesic and anti-inflammatory properties, so it may be useful as a DED medication [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…73 Second, GBT's antianxiety and sedative effects may indirectly influence the activity of the lacrimal glands, thereby affecting tear secretion. 65 The topography of the cornea in different groups was evaluated to understand the responses of the various materials used to treat DE (Figure 5i). The uniform green color map denotes healthy corneas without any aberration, while the color varies from orange to red with increasing aberration.…”
Section: Synthesis and Characterization Of Thiolated Gelatinmentioning
confidence: 99%
“…In a study of rats and mice, the expression of AQP5 was up-regulated after crushed sciatic nerve injury, and neuropathic pain is one of the main symptoms of sciatic nerve injury, suggesting that AQP5 may be related to neuropathic pain [40]. In addition, topical administration of gabapentin was found to alleviate neuropathic ocular pain by inducing AQP5 expression in the lacrimal gland, and resveratrol was found to mitigate neuropathic pain by inhibiting AQP5 activation caused by chronic contractile injury [16,135]. Moreover, studies have indicated that AQP5 colocalizes with AQP2 in the kidney, and AQP5 can also regulate AQP2 expression, which is associated with neuropathic pain [15,41,136].…”
Section: Aqp5mentioning
confidence: 99%